Gunungan Wayang Kulit Purwa: A Study of Aesthetic Form, Philosophy, and Utilization in Implementing Educational Values (Universitas Negeri Semarang, 2022)
The entry of globalization and modernization into Indonesia has gone hand in hand with the emergence of attitudes contrary to Javanese cultural values. Learning media can generate new desires and interests, increase motivation and stimulation of learning activities, and even psychologically affect students. Introducing the philosophy of gunungan wayang will be more effective if it is taught at schools. This study aims to describe and analyze how Gunungan Wayang Kulit Purwa can instill educational values ​​in SMA N 1 Cepiring. The research method used qualitative research with a case study design. The process of collecting data employed observation, interviews, and literature study. According to Miles and Huberman, data reduction, data presentation, and concluding were carried out with three activity lines. The results of this study are in the form of wayang creations or specifically the parts of gunungan, and they are used to deliver educational messages to the students. The character values instilled in the students are responsibility, curiosity, and honesty. The significance of this research is as an overview of the benefits of Gunungan Wayang Kulit Purwa to instill educational values ​​in students at SMA N 1 Cepiring.